Host factors that modify Plasmodium falciparum adhesion to endothelial receptors. Issue 1 (December 2017) - Mahamar, Almahamoudou; Attaher, Oumar; Swihart, Bruce; Barry, Amadou; Diarra, Bacary; Kanoute, Moussa; Cisse, Kadidia; Dembele, Adama; Keita, Sekouba; Gamain, Benoît; Gaoussou, Santara; Issiaka, Djibrilla; et al.
Abstract P. falciparum virulence is related to adhesion and sequestration of infected erythrocytes (IE) in deep vascular beds, but the endothelial receptors involved in severe malaria remain unclear. In the largest ever study of clinical isolates, we surveyed adhesion of freshly collected IE from children under 5 years of age in Mali to identify novel vascular receptors, and examined the effects of host age, hemoglobin type, blood group and severe malaria on levels of IE adhesion to a panel of endothelial receptors. Several novel molecules, including integrin α3β1, VE-cadherin, ICAM-2, junctional adhesion molecule-B (JAM-B), laminin, and cellular fibronectin, supported binding of IE from children. Severe malaria was not significantly associated with levels of IE adhesion to any of the 19 receptors. Hemoglobin AC, which reduces severe malaria risk, reduced IE binding to the receptors CD36 and integrin α5β1, while hemoglobin AS did not modify IE adhesion to any receptors. Blood groups A, AB and B significantly reduced IE binding to ICAM-1. Severe malaria risk varies with age, but age significantly impacted the level of IE binding to only a few receptors: IE binding to JAM-B decreased with age, while binding to CD36 and integrin α5β1 significantly increased with age.